Desenvolvimento e validação de método multirresíduo, empregando GC-ECD E GC-MS, para a investigação de pesticidas em morango, maçã e uva - Mayer, Karine Kochhann Rhoden (2005)
Pesticides use is still the main strategy used in the field for the combat and the prevention of agricultural plagues, guaranteeing enough food and of quality for the population. In the culture of fruits, especially in strawberries, apples and grapes, the consequent contamination by pesticide residues has the been objective of constant concern in the ambit of the public health. Due to the toxicity associated with these substances quality of the produced victuals is necessary in order to prevent possible risks to the consumer. In the present study, a multiresidue method was developed and validated for the quantification of the pesticides chlorothalonil, chlorpyrifos, captan, procymidone, kresoxim methyl, iprodione, fenpropathrin, deltamethrin and azoxystrobine using Gas Chromatography with Electron Capture Detection (GCECD) in different matrices (strawberry, apple and grape). Gas Chromatography coupled with Mass Spectrometry (GC-MS) was used for the investigation of the pesticides present in the samples. Some extraction conditions were appraised, such as type and volume of solvents, amount of sample and purification of the extract. The extraction with 1:1 (v/v) mixture of ethyl acetate/n-hexane, in ultraturrax, followed by purification in florisil® columns and reduction of the extract volume by evaporation of the solvent presented the best results. The optimized conditions for the GC-ECD system were: capillary column DB-5; programming of the oven temperature: 80 °C - 2 min, 180 °C (10 °C min-¹)- 1 min, 255 °C (8 °C min-¹); 315 °C (15 °C min-¹) 4.25 min, pressure of the carrier gas (He) 21 psi; injection volume 1 μL; injetor temperature 270 °C and of the detector to 330 °C. For the analysis by GC-MS the used conditions were: capillary column VF - 5MS, Factor Four/MS (Varian) with 5 m of EZ-Guard®; programming of the column temperature: 80 °C (25 °C min-¹), 180 °C (5 °C min- ¹), 280 °C - 10 min, pressure of the carrier gas 10 psi; injection volume 1 μL, in the splitless mode; temperature of the manifold of 80 °C and of the interface of 230 °C, energy of 600 eV applied to the ion multiplier and ion-trap temperature of 200 °C. In the validation of the method the following parameters were verified: detection limit (LOD), quantification limit (LOQ), linearity, precision (repeatability and intermediary precision) and recovery. LODs and LOQs of the instrument varied from 2.5 to 18.7 μg L-¹ and from 5.0 to 25.0 μg L-¹, except for the deltamethrin (0.2 and 0.8 μg L-¹), respectively. For the analyzed samples obtained LOQs values from 0.6 to 15.6 mg kg-1 were obtained for the pesticides in study. The analytical solutions were prepared in "blank extract" of the fruits to compensate for the observed matrix effect, being obtained analytical curves with r2 ≥0.9925. The precision assays supplied acceptable results, with RDS values between 0.3 and 14.8%. Recoveries from 85.4 to 111.3% were obtained for the studied matrices, except for captan in grape (70.1%). The results obtained in the validation allowed us to conclude that the method is adaptable for the determination of these compounds in strawberries, apples and grapes, being that the method was applied in the analysis of 21 samples obtained in the trade. Pesticides presences were verified in 72.7% in the strawberry samples, 80% of the apple and grape samples, where chlorpyrifos, chlorothalonil, captan, iprodion, deltamethrin and fenpropathrin were found.